A 3D Biohybrid Real‐Scale Model of the Brain Cancer Microenvironment for Advanced In Vitro Testing. Issue 10 (23rd August 2020) - Tricinci, Omar; De Pasquale, Daniele; Marino, Attilio; Battaglini, Matteo; Pucci, Carlotta; Ciofani, Gianni
Abstract: The modeling of the pathological microenvironment of the central nervous system (CNS) represents a disrupting approach for drug screening for advanced therapies against tumors and neuronal disorders. The in vitro investigations of the crossing and diffusion of drugs through the blood–brain barrier (BBB) are still not completely reliable, due to technological limits in the replication of 3D microstructures that can faithfully mimic the in vivo scenario. Here, an innovative 1:1 scale 3D‐printed realistic biohybrid model of the brain tumor microenvironment, with both luminal and parenchyma compartments, is presented. The dynamically controllable microfluidic device, fabricated through two‐photon lithography, enables the triple co‐culture of hCMEC/D3 cells, forming the internal biohybrid endothelium of the capillaries, of astrocytes, and of magnetically‐driven spheroids of U87 glioblastoma cells. Tumor spheroids are obtained from culturing glioblastoma cells inside 3D microcages loaded with superparamagnetic iron oxide nanoparticles (SPIONs). The system proves to be capable in hindering dextran diffusion through the bioinspired BBB, while allowing chemotherapy‐loaded nanocarriers to cross it. The proper formation of the selective barrier and the good performance of the anti‐tumor treatment demonstrate that the proposed device can be successfully exploited as a realistic in vitro model for high‐throughput drug screening in CNS diseases. Abstract : This real‐scale 3D‐printed biohybrid microfluidic device can mimic the glioblastoma microenvironment at level of the blood–brain barrier. It allows the triple co‐culture of endothelial cells, astrocytes, and magnetically‐driven spheroids of U87 glioblastoma cells. The device demonstrates to be successfully exploitable as a realistic in vitro model for high‐throughput drug screening in central nervous system diseases.